Attitudes of Baghdad University students towards extremism - علي عودة محمد; سيف محمد رديف; بيداء هاشم جميل; ميسون كريم ضاري; بشرى عثمان أحمد; حيدر كامل مهدي (Zanco Journal of Humanity Sciences)
The current research aims to identify the attitude towards extremism in general and according to its dimensions among students of the University of Baghdad. And to identify the significance of differences in the attitude towards extremism in general and according to its dimensions depending on the gender variable(male, female), and according to the variable of the academic stage (first, fourth).